2016
DOI: 10.1007/s00595-016-1352-2
|View full text |Cite
|
Sign up to set email alerts
|

Modified Marcy repair for indirect inguinal hernia in children: a 24-year single-center experience of 6826 pediatric patients

Abstract: Modified Marcy hernia repair is a safe and effective procedure for inguinal hernia in children with excellent outcomes and a low incidence of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 14 publications
0
57
1
2
Order By: Relevance
“…[ 4 8 ] As a result, some surgeons are also in favor of open surgery. A 24-year study by Pogorelić et al [ 9 ] from Japan found that Marcy hernia repair is a safe and effective procedure for inguinal hernia in children with excellent outcomes and a low incidence of recurrence. Indeed, open repair procedure, as a gold standard for hernia repair, remains the mainstay of treating pediatric bilateral inguinal hernia at present.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 8 ] As a result, some surgeons are also in favor of open surgery. A 24-year study by Pogorelić et al [ 9 ] from Japan found that Marcy hernia repair is a safe and effective procedure for inguinal hernia in children with excellent outcomes and a low incidence of recurrence. Indeed, open repair procedure, as a gold standard for hernia repair, remains the mainstay of treating pediatric bilateral inguinal hernia at present.…”
Section: Introductionmentioning
confidence: 99%
“…For many years, the golden standard of treatment of inguinal hernia was high ligation and division of the sac by an open inguinal approach. 1 In 1990s, when laparoscopic surgery became more popular among pediatric surgeons, many successful laparoscopic inguinal hernia repairs were reported. 2 Many laparoscopic techniques have been described but none become golden standard for inguinal hernia repair in children.…”
Section: Pediatric Surgery University Hospital Of Split Spinciceva mentioning
confidence: 99%
“…4,5 Recently, published meta-analysis had shown the rate of recurrence of 0.7% which is very similar to open surgery. 1,4 An incidence of complications in hands of experienced laparoscopic pediatric surgeon is very low. The most common reported complications are injury of blood vessels, recurrence, hydrocele formation, knot reaction, severe pain, and scrotal swelling.…”
Section: Pediatric Surgery University Hospital Of Split Spinciceva mentioning
confidence: 99%
“…Inguinal hernia repair is one of the most common surgical procedures performed in children worldwide [3, 4]. Inguinal hernia is a relatively common surgical problem in children, with a reported incidence ranging from 0.5 to 4.5% [5, 6]. The cumulative incidence of inguinal hernia repair is 7% in male patients and 1% in female patients for children aged less than 15 years [7].…”
Section: Discussionmentioning
confidence: 99%